Acute Hemorrhagic Edema of Infancy: A Case Report Case Report¬ - Hakan Turan; Ayşegül Turan (Güncel Pediatri)
Introduction: Acute hemorrhagic edema of infancy is a rare subtype of leukocytoclastic vasculitis. It is characterized by target-like hemorrhagic plaques with edema. Lesions are localized to face and distal extremities. It usually heals spontaneously without any sequelae.Case Report: Herein, an 8-month-old girl infant with acute hemorrhagic edema of infancy was presented. Conclusion: Both dermatologists and pediatricians must be familiar with this rare type of leukocytoclastic vasculitis. We believe that this familiarity will eliminate unnecessary treatment and anxiety about the disease (Journal of Current Pediatrics 2011; 9: 50-2)